The theological foundation of Christian ethics: methodological issues - Blocher, Henri (European journal of theology, 2015)
The proposed inquiry starts from the conviction that theology and a Christian reflection on basic issues in ethical theory cannot be separated, nor can method from content. Since both rest on the bedrock subfoundation of evangelical faith (fides quae), theology may comment on first-rank decisions concerning the constitutive principle of the ethical (duty, goodness/happiness?), on the target of moral evaluation and training (act or habitus, individuals or communities?), and on the sources of guidance (proper hermeneutics, worship, theology - revealed or natural -, historical context?). The main partners in the dialogue include Oliver O'Donovan, Paul Ricoeur and Helmut Burkhardt, while some attention is devoted to the debate around Brian Brock's recent book.